Fault tolerant design of a field data modular readout architecture for railway applications. (October 2015) - Fort, Ada; Mugnaini, Marco; Vignoli, Valerio; Gaggii, Vittorio; Pieralli, Moreno
Abstract: Modern data acquisition systems used to collect sensor signals are usually designed taking into consideration performance and operating parameters which are mainly related to sensitivity, selectivity, resolution and stability over time. In addition to such important features, field application systems should also respond to other constraints like reliability and availability and additionally, depending on the specific application, to some peculiar requirements in terms of safety. The present paper is addressed to supply an overview of the implications, during a sensor input/output hardware module design, of such parameters as the safety integrity level. The discussion involves the overall system design once integrated with availability considerations. In this manuscript, considerations concerning the on board software implementation are omitted without loss in generality. The study has been developed taking into account solutions suitable for railway applications like signaling or crossing detection systems. Highlights: The possibility to provide designers with standard sample safe solution. Addressing the design concept of a readout interface according to highly diffused standards. Comparison of multiple solutions in terms of RAMS parameters. Provide to designers a general simple methodology to approach similar problems.